The comparison between low level infra-red laser and triamcinolone acetonide mouth rinse in treatment of oral lichen planus lesions - Mandana Khatibi; Arash Azizi; Abbas Kamali; Soheila Mohammadian (Tehran University of Medical Sciences, 2018)
Background and Aims:The erosive and ulcerative forms of Oral lichen planus causes pain and irritation, affects the nutrition and biological quality of the patient. Considering the high prevalence of the disease, the complications of conventional treatments and the resistance to classical drug therapy, the aim of this study was to compare the effect of infrared low level laser and triamcinolone acetonide mouth rinse on treatment of oral lichen planus lesions. Materials and Methods:In this double blind clinical trial, 24 patients were selected randomly according to the inclusion and exclusion criteria and divided into two groups of 12. Before and after the study, pain and burning sensation index (VAS), apparent shape and score of the lesion and size of the lesion were recorded in the patients. We treated the first group with low level infrared laser (810 nm) twice a week with 0.5-2 j/cm2 energy density and 300 mW/cm2 power density up to a maximum of 10 sessions. For the second group, we prescribed a mouth rinse of triamcinolone acetonide 0.2% four times a day with antifungal drugs for a month. Then, the study`s criteria were recorded after the completion of treatment. All data were statistically analyzed using the repeated measure ANOVA test to compare the quantitative changes over time, The Mann-Whitney U test was used to compare the rank variables between two groups at any time and Friedman test for each group between different times. Results: There was no significant difference between the groups in terms of severity of pain (P=0.255), score and size (P=0.186), and appearance (P=0.178) of the lesions among two groups. Although the two groups showed a significant decrease in all three indicators. Conclusion:Considering that in both groups, all three indices were improved and these improvements were similar, it seems that laser therapy can be effective. It could be used as a therapeutic alternative in treating patients with OLP (Oral Lichen Planus) especially in cases with contraindication in corticosteroid administration or lack of appropriate therapeutic response or when there is resistance to treatment.